Curvas de resistência ao crescimento de trinca em corpos de prova SE(T) utilizando a técnica de normalização - Menezes, João Teixeira Oliveira de. (2018)
Structural assessment of structures and equipment that contain cracks must use Fracture Mechanics concepts and methodologies. Depending of the material behavior, Linear-Elastic Fracture Mechanics or Elastic-Plastic Fracture Mechanics can be used. In general, structures and equipment used in the Oil & Gas industry present elastic-plastic behavior. So, these materials must be analyzed through the Elastic-Plastic Fracture Mechanics. However, there are different types of specimen geometries and loading that introduces different constraint level at the crack tip. Works indicate that pipelines used to transport and conduct oil and gas with axial and circumferential cracks are better represented by low constraint specimens, more precisely by SE(T) specimens. Many methodologies to determine crack growth resistance curves of elastic-plastic materials are known, as the unloading compliance method and the normalization technique, being the latter methodology, few used in low constraint specimens. Crack growth resistance curves through the normalization method were determined using SE(T) specimens and then they were compared with obtained by unloading compliance technique. Besides that, aiming to compare different constraint levels, a comparison between SE(T) and SE(B) specimens of the same material was made. Results indicate that the normalization method after some little modifications presented good results for the SE(T) specimens and that the fracture toughness is influenced by the constraint level.